In silico and in vitro inhibition of α- glucosidase and α-amylase by compounds from culinary herbs and spices, for possible treatment of type 2 diabetes - Apostolides, Zeno (University of Pretoria, 2021)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2020.